Model Specification Tests Against Non-Nested Alternatives - James G. MacKinnon (Queen's University, Department of Economics, 1983)
Non-nested hypothesis tests provide a way to test the specification of an econometric model against the evidence provided by one or more non-nested alternatives. This paper surveys the recent literature on non-nested hypothesis testing in the context of regression and related models. Much of the purely statistical literature which has evolved from the fundamental work of Cox is discussed briefly or not at all. Instead, emphasis is placed on those techniques which are easy to employ in practice and are likely to be useful to applied workers.
Keywords: C10; C12; 330; Cox test; nonnested hypotheses; J test; specification tests; nonnested hypothesis test